Optimization and application of a high-resolution melting protocol in the characterization of avian infectious laryngotracheitis virus = Optimización y aplicación de un protocolo de desnaturalización de alta resolución en la caracterización del virus de la laringotraqueítis infecciosa aviar - Rojas, María Florencia; Konig, Guido Alberto; Vagnozzi, Ariel Eduardo; Vera, Federico Sebastian; Scolaro, Luis Alberto; Craig, María Isabel (Elsevier, 2020)
A previous sequence analysis of a US5 gene fragment of infectious laryngotracheitis virus (ILTV) performed in an Argentinian epidemiological study allowed to differentiate between wild and vaccine strains. This analysis also defined five ILTV haplotypes with specific variations at positions 461, 484, 832, 878 and 894 of the US5 gene. This characterization of viral strains may also be accomplished using the High-Resolution Melting Analysis (HRMA), which has been described as an effective, fast and sensitive method to detect mutations in PCR products. In the present study, an HRM protocol was developed with the aim of characterizing the circulating ILTV strains in Argentina. The specificity of this tool was confirmed in different DNA diluents, without interference from heterologous DNA or other cellular metabolites. Additionally, the salt concentration in the elution buffer used for DNA extraction did not alter the curve profiles. Higher concentrations of DNA (Ct ≅ 26.0) displayed well-defined curve profiles, whereas lower concentrations (Ct ≅ 32.5) exhibited more heterogeneous curves. The HRMA showed 97.49% concordance with the reference technique, i.e., sequencing. The HRM protocol has the capability to perform DNA amplification prior to its characterization. Thus, eventually this technique may be used simultaneously as a diagnostic tool. This advantage implies a significant reduction in the time and effort involved in sample processing.